KONSEP PENDIDIKAN KARAKTER ISLAMI MENURUT IMAM AL – GHAZALI DAN RELEVANSINYA DALAM MENGATASI KRISIS MORAL REMAJA - Syaharani Oktavia; Muhamad Ikhsanudin; Suhartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the concept of Islamic character education according to Imam Al-Ghazali and its relevance in overcoming the moral crisis among adolescents. The background of this research is the increasing moral degradation among teenagers in the era of globalization and digital technology, which is reflected in the decline of politeness, weak self-control, low moral awareness, and the rise of deviant behavior. In addition, education is still more oriented toward cognitive achievement, while moral and spiritual development has not been optimally implemented. This research aims to analyze the concept of Islamic character education according to Imam Al-Ghazali and its relevance in addressing adolescent moral crises. This study employed a qualitative approach with a library research method. The primary data sources were Imam Al-Ghazali’s works, particularly Ihya’ ‘Ulum al-Din and Ayyuhal Walad, while secondary data were obtained from books, journals, and other relevant scientific references. The data were analyzed using descriptive-analytical methods. The results of the study indicate that Imam Al-Ghazali’s concept of character education emphasizes the integration of knowledge and practice through purification of the soul (tazkiyatun nafs), habituation of good morals, and the exemplary role of educators. This concept is considered highly relevant in overcoming the moral crisis among adolescents because it can foster moral and spiritual awareness and shape inner consciousness that consistently encourages positive behavior.